Small Ubiquitin-Like Modifier 4 (SUMO4) Gene M55V Polymorphism and Type 2 Diabetes Mellitus: A Meta-analysis Including 6,823 Subjects - Li, Yan-yan; Wang, Hui; Yang, Xin-xing; Geng, Hong-yu; Gong, Ge; Kim, Hyun Jun; Zhou, Yan-hong; Wu, Jing-jing (Frontiers in Endocrinology, 2017)
Background Many studies suggest that the small ubiquitin-like modifier 4 (SUMO4) M55V gene polymorphism (rs237025) may be associated with an increased risk of type 2 diabetes mellitus (T2DM). However, due to other conflicting results, a clear consensus is lacking in the matter. Objective and methods A meta-analysis consisting of 6,823 subjects from 10 studies was conducted to elucidate relationship between the SUMO4 M55V gene polymorphism and T2DM. Depending on the heterogeneity of the data, either a fixed or random-effects model would be used to assess the combined odds ratio (ORs) and their corresponding 95% confidence interval (CI). Results SUMO4 gene M55V polymorphism was significantly associated with T2DM in the whole population under allelic (OR: 1.18, 95% CI: 1.10–1.28, P = 1.63 × 10−5), recessive (OR: 1.59, 95% CI: 1.14–2.23, P = 0.006), dominant (OR: 0.815, 95% CI: 0.737–0.901, P = 6.89 × 10−5), homozygous (OR: 1.415, 95% CI: 1.170–1.710, P = 0.0003), heterozygous (OR: 1.191, 95% CI: 1.072–1.323, P = 0.001), and additive genetic models (OR: 1.184, 95% CI: 1.097–1.279, P = 1.63 × 10−5). In our subgroup analysis, a significant association was found again in the Chinese population, but not in Japanese or Iranian population. Conclusion SUMO4 gene M55V polymorphism may correlate with increased T2DM risk. Chinese carriers of the V allele of the SUMO4 gene M55V polymorphism may be predisposed to developing T2DM.